Exploring the clinical and histopathological characteristics on breast phyllodes tumors predictors and prognosis in a real world - Han, Ye; Yu, Hong; Li, Congyi; Jiang, Wei; Shan, Huilian (Frontiers in Oncology, 2025)
Study objectivePhyllodes tumors of the breast (PT) are rare fibroepithelial tumors with varied clinical and histopathological characteristics, and standardized with wide margins in surgery, a systemic retrospective study of PT could improve our understanding of prognosis.DesignWe conducted a retrospective study spanning 2008-2021, which included 333 cases of PT for chart review. We used logistic regression and comparison tests to evaluate the association between clinical features and local recurrence (LR), as well as to summarize overall survival (OS) and disease-free survival (DFS).SettingPhyllodes tumors of the breast exhibit a propensity for a higher recurrence rate. The surgical protocol advocates for achieving wide margins (>1 cm), which presents challenges in clinical practice due to the ambiguity in defining such margins.ParticipantsA retrospective screening identified 333 cases of PT for inclusion in the study. Comprehensive data for this analysis was extracted from the clinical patient records.InterventionsPost-operation, all cases were subjected to a standardized protocol of regular follow-up , with subsequent documentation of follow-up data.Main outcome measuresAt a median follow-up of 79 (inter-quartile range: 28-109) months, recurrence occurred in 9.7% (19/196) of benign, 18.4% (18/98) of borderline, and 28.2% (11/39) of malignant tumors. Local recurrence was not reduced with enlarged margin width (<1 cm vs. >1 cm: odds ratio (OR)=0.84; 95% CI, 0.48 to 1.47; p=0.53), but it was associated with age (<40 vs. >40: OR=2.04; 95% CI, 1.13 to 3.68; p=0.01). LR was significantly correlated with mitosis (<5/HFP vs. >=5/HFP: OR=0.56; 95% CI, 0.32 to 0.98; p=0.003), stromal overgrowth (yes vs. no: OR=0.43; 95% CI, 0.32 to 0.98; p=0.014), and stromal atypia (mild vs. marked: OR=0.59; 95% CI, 0.30 to 1.17; p=0.003).Result and conclusionThis retrospective study confirmed that recurrence and prognosis were not associated with wide margins in the real world, as suggested by previous guidelines, possibly due to the influence of characteristics such as age, stromal overgrowth, stromal atypia, and mitosis.